A Proposal for Key Sustainability Credit Assessment Criteria to Update and Develop International Ranking Systems for Green Buildings - Maryam Mollazadeh Yazdani (صفه)
As they are mainly focused on the environmental side of sustainability, a concentration on green certificates’ credit systems risks neglecting the bigger picture. From this point of view, it is necessary to develop key credit criteria and define a framework for key measures in a way that the triple aspects of sustainability are assessed in a balanced manner in ranking. The aim of this research is to propose measurable, key credit criteria to correspond with all three aspects, in order to update current ranking systems. In order to do so, and after determining the objectives of sustainable building based on the three aspects of sustainability, and the recognition of key criteria through a worldwide study of eight ranking systems, the credit criteria were tested against the three measures in order to spot overlaps and shortages. On that basis, seven key criteria were recognised: energy, water, sustainable site, materials, waste and pollution, internal air quality, and the development and management of new systems. Of those, the two latter cover social parameters, and the five former cover environmental ones. Furthermore, five complementary measures were recognised: education and awareness of sustainability, and protection of physical resources covering the social parameter, and initial, consumption and recycling costs covering the economic parameter. These were referred to in the research but were not found among studied tools. A total of 12 key economic, social and environmental criteria are, therefore, proposed to form a basis of environmental building assessment, in order to update and develop ranking systems.